Your money or your time? How both types of scarcity matter to physical activity and healthy eating. (January 2017) - Venn, Danielle; Strazdins, Lyndall
Abstract: Rationale: Lack of time is one of the most common reasons people give for not exercising or eating healthy food, yet few studies explicitly test its relationship with health behaviours. Objective: Conceptualising time as a social determinant we estimate how scarcity — of income or time — generate barriers to health behaviours. Methods: Using longitudinal, nationally-representative survey data on Australians aged 25–54 years, our design addresses endogeneity and reverse causation by considering how new episodes of scarcity are related to changes in healthy eating and physical activity. Regression models estimated how scarcity of income (low income or feeling poor) or time (heavy time commitments or feeling rushed for time) predicted change over two consecutive years. Results: We find that both income and time scarcity reduce physical activity and, in some cases, lead people to consume less fruit and vegetables, eat out more and eat more discretionary calories (food high in salt, sugar or fat). Further, income and time scarcity operate independently to constrain healthy choices, although for more than one in ten people they synergistically increase risk. Conclusion: Because income and time scarcity are patterned by socio-economic status and gender, our results underline the need to address both if public health interventions are to be more effective and fair. Highlights: Healthy behaviour requires time as well as income. Onset of scarcity (time or income) predicts change in physical activity and diet. When time and income scarcity combine they amplify unhealthy behaviour change. Time scarcity is a socially-patterned determinant of physical activity and diet.